HERMES: unveiling obscured star formation - the far-infrared luminosity function of ultraviolet-selected galaxies at z similar to 1.5 - Heinis, S; Buat, V; Bethermin, M; Aussel, H; Bock, J; Boselli, A; Burgarella, D; Conley, A; Cooray, A; Farrah, D; Ibar, E; Ilbert, O; et al. (2013)
We study the far-infrared and sub-millimetre properties of a sample of ultraviolet (UV) selected galaxies at z ̃ 1.5. Using stacking at 250, 350 and 500 μm from Herschel Space Observatory Spectral and Photometric Imaging Receiver (SPIRE) imaging of the Cosmological Evolution Survey (COSMOS) field obtained within the Herschel Multi-tiered Extragalactic Survey (HERMES) key programme, we derive the mean infrared (IR) luminosity as a function of both UV luminosity and slope of the UV continuum μ. The IR to UV luminosity ratio is roughly constant over most of the UV luminosity range we explore. We also find that the IR to UV luminosity ratio is correlated with β. We observe a correlation that underestimates the correlation derived from low-redshift starburst galaxies, but is in good agreement with the correlation derived from local normal star-forming galaxies. Using these results we reconstruct the IR luminosity function of our UV-selected sample. This luminosity function recovers the IR luminosity functions measured from IR-selected samples at the faintest luminosities (LIR ~ 1011 L⊙), but might underestimate them at the bright-end (LIR ≥ 5 × 1011 L̇). For galaxies with 1011 < LIR/L· < 1013, the IR luminosity function of an UV selection recovers (given the differences in IR-based estimates) 52-65 to 89-112 per cent of the star formation rate density derived from an IR selection. The cosmic star formation rate density derived from this IR luminosity function is 61-76 to 100-133 per cent of the density derived from IR selections at the same epoch. Assuming the latest Herschel results and conservative stacking measurements, we use a toy model to fully reproduce the far-IR luminosity function from our UV selection at z ~ 1.5. This suggests that a sample around 4 mag deeper (i.e. reaching u* ~ 30 mag) and a large dispersion of the IR to UV luminosity ratio are required. © 2012 The Authors. Published by Oxford University Press on behalf of the Royal Astronomical Society.